Unveiling the Secrets of the Inca Kingdom: Insights from Archaeological Findings in Peruvian History - Purwanti, Winda (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This comprehensive research delves into the analysis of the Inca Kingdom in Peru through the lens of archaeological findings, exploring its historical, cultural, and societal dimensions. The study encompasses a multidisciplinary approach, combining archaeological, historical, and anthropological methodologies to unravel the mysteries of this ancient civilization. The investigation begins by examining the rise, peak, and decline of the Inca civilization, detailing key historical events and developments. Archaeological discoveries at significant sites such as Machu Picchu, Sacsayhuaman, and Ollantaytambo shed light on the architectural achievements and urban planning sophistication of the Inca. These findings reveal their advanced engineering skills and urban organization, showcasing the societal, political, and religious complexities of the empire. The analysis further scrutinizes specific artifacts, structures, and their functions, offering insights into daily life, cultural practices, and technological advancements within the Inca society. The political organization, social classes, economic activities, religious beliefs, and cultural elements are meticulously examined to paint a vivid picture of the Inca civilization's multifaceted nature. The methodologies employed in archaeological research, from excavation techniques to scientific analyses like carbon dating, geospatial analysis, and ethnographic studies, contribute to the comprehensive understanding of the Inca Kingdom's complexities and historical significance. The essay critically explores the implications of these archaeological findings, analyzing their lasting impact on the cultural and historical identity of Peru and the world